In-situ catalytic effect of potassium on petroleum coke gasification with a Mn ore-based oxygen carrier. (15th December 2021) - Liu, Xianyu; Ma, Jiandong; Hong, Qi; Ma, Shiwei; Ge, Huijun; Song, Tao
Highlights: Potassium as a catalyst for CLG to accelerate coke gasification. Two potassium introduction modes were applied. In-situ catalytic effect of potassium was investigated and compared. Effects of temperature, oxygen carrier to fuel ratio and cycles are evaluated. CLG with coke modified by potassium achieves the highest average carbon conversion. Abstract: Potassium was used as a catalyst for Chemical Looping Gasification (CLG) process in order to accelerate petroleum coke gasification. Two catalytic modes were applied, one was to use potassium to modify coke and another one was to a Mn ore based oxygen carrier. The in-situ catalytic effect of potassium during CLG process was experimentally evaluated in a fluidized bed. The influences of reaction temperature, oxygen carrier to fuel ratio, potassium introduction modes and cycles on syngas yields and distribution, carbon conversion and potassium evolution were investigated. Results indicated that both catalytic modes can accelerate coke conversion. Beneficial coke conversion was brought into play after several cycles' activation for the potassium-modified Mn ore oxygen carrier applied for CLG process. Its activation with cycles led to an increase of the average carbon conversion rate, obtaining a stable value of 4.39%/min, higher than the one of 3.91%/min for the condition without potassium addition. Part of potassium on the surface of oxygen carrier was partially lost in the initial cycles and then fixed on the oxygen carrier particles. The remaining potassium existed in the form of K2 Si4 O9 . The catalytic model of using the potassium to modify coke for CLG process accelerated coke conversion remarkably, obtaining an average carbon conversion rate of 7.8%/min, which is 1.78 times higher than that of using potassium to modify the Mn ore. Besides, the potassium into the reaction process had little effect on the oxygen carrier's reactivity, but accelerated the water gas shift reaction, producing more H2 and less CO in the syngas.